LANGUAGE AND PARTIALITY OF MEDIA: TRANSITIVITY ANALYSIS OF BLASPHEMY NEWS REPORTED BY KOMPAS WEBSITE - Nuryadi Nuryadi (Fakultas Komunikasi, Sastra, dan Bahasa, 2022)
The present study aims to describe the type of transitivity, logical meaning and point of view from news about blasphemy conducted by Basuki Tjahaja Purnama (BTP), the former governor of Jakarta reported by Kompas, a news website. The present study is grounded under qualitative research with a functional discourse analysis approach. Data is obtained from news about BTP which were published from September to November 2016. The results of the analysis suggest that the most dominant type of transitivity was verbal process, the most dominant participant was verbiage, the most dominant circumstant was location, while the logical meanings found were 178 data out of 220 (80.91%). Discourse field is analyzed through the verbal process which contained rebuttals, clarifications and explanations that BTP did not mean to insult Islam. The social context links the blasphemy of Islam with politics. Kompas website intends to state that there are parties who deliberately take advantage of the blasphemy of Islam for political purposes. Discourse actors are divided into roles, social distance and social status. The prominent roles and social status came from Islamic religious leaders, especially from the religious organizations whose opinion was more favorable to BTP's position while social distance narrates BTP's closeness to Muslims, especially ones in Jakarta.